“Be patient, dear mother … wait for me”: the neo-infirmity film, female illness and contemporary cinema - Gallagher, Mark (Taylor & Francis, 2009)
In social reality, illness and death occur in myriad ways, yet Hollywood films have historically preferred spectacular, violent death over realist depictions of the terminal stages of life. Yet an ever-growing number of popular films, which I term neo-infirmity films, incorporate episodes of women characters debilitated by illness or injury. Operating at the intersection of melodrama and realism, the scenes are instrumental in staging contemporary cinema's gender politics. I argue that women's deathbed and hospital-bed scenes in contemporary cinema validate anew the maternal role and the figure of the mother, transporting the woman-centered discursive space of melodrama into narrative terrain often hostile to women's presence. Through this relocation, the films emphasize her importance to sons in particular (and less often to daughters, husbands, and the larger family unit). Many such scenes simultaneously undermine women's agency, reducing mothers to principally symbolic, literally immobile roles. Ailing women can become catalysts for male psychological transformation occurring through grief, action, or both in combination. In all, such scenes speak to continued ambivalence surrounding women's representation in popular cinema, and to continued patrolling of the boundaries of female power. This essay compares selected texts from contemporary Hollywood cinema, alongside three parallel discourses that also deploy melodramatic modes of articulation: nonfiction amateur video as relayed via television news programs, international art cinema, and US independent cinema. Arguing for homologies across multiple fields of textual production, I seek through this comparison to generate insights into the cultural work done by filmic representation.